Reconstruction of the chronology, authorial position, and design themes of architect Rastko Radulović in French design studios (1959–1964; 1972–1975) - Anđelković, Goran V. (Arhitektura i urbanizam, 2025)
Serbian-French relations have so far been the subject of research by both domestic and international authors. Narrower and more specific thematic areas – such as Serbian-French architectural connections – still lack a comprehensive and systematic overview within architectural history and theory. The significance of researching these relations lies in identifying both the direct and indirect French influences on the Serbian architectural and cultural context, as well as on the development of Serbian architecture and the aesthetic refinement of the authorial expression of Serbian architects. This paper focuses on two professional engagements of architect Rastko Radulović (1933–2005) in France – the first in Gоuyon’s design studio (1959–1964) and the second in Delb’s design studio (1972–1975). The aim of the research is to reconstruct Radulović’s professional engagement in France, based on partially preserved project documentation and hand sketches, and to determine his authorial contribution to contemporary architecture. The research rests on the hypothesis that his relatively brief professional experiences in France had a formative impact on the development of new formal and spatial concepts within Radulović’s oeuvre. The methodology applied encompasses comparative analysis, deductive reasoning, and a critical review of both primary and secondary sources, with the aim of reconstructing, with precision, the chronology, authorial position, and design themes during his professional engagement in French design studios in the 1960s and 1970s. The findings indicate that Radulović, even within a short period, contributed to the opening of new design themes that corresponded with the contemporary tendencies and critiques of the dominant modernist discourse. The contribution of this research lies in its systematic reconstruction of the chronology, authorial position, and design themes of Radulović’s professional engagement in French design studios, while also pointing to further directions of inquiry that may contribute to a deeper contextualized understanding of Serbian-French architectural connections.